SIMULATION OF HIGHER EDUCATIONAL ESTABLISHMENT COMPETITIVENESS - Ryzhkov, Alexander S.; Koshkin, Konstantyn V.; Knyrik, Natalia R.; Ryzhkov, Rostyslav S. (International Journal of Research -GRANTHAALAYAH, 2017)
The success of International Joint Educational Programs of the Educational Establishments based on effective management. This makes a need for predicting the competitiveness indicators in order to analyze different strategies for the expansion of higher education establishments and the picking up the best scenarios of its market play. The simulation methodology makes possible to performe analysis management that contains elements of actions that influenced by random factors. Using the method of system dynamics as the main tool is due to the complexity of the strategic alternatives selection in a dynamically developing situation, under conditions of external and internal uncertainty. The initial state of performed simulation was based on the parameters that define the market share and the number of potential students of the joint educational program between Admiral Makarov National University of Shipbuilding and partner in Zhejiang City, China. Sensitivity analysis experiments allow determining the influence of the initial hypotheses and the key parameters values on the model output parameters of the interference of competitiveness factors under uncertainty conditions. This significantly improves the effectiveness of management processes.